The Pulmonary Veins of the Pig as an Anatomical Model for the Development of a New Treatment for Atrial Fibrillation. (25th December 2013) - Vandecasteele, T.; Vandevelde, K.; Doom, M.; Van Mulken, E.; Simoens, P.; Cornillie, P.
Summary The layout of the porcine atriopulmonary junction and immediately adjacent structures was investigated by gross anatomical and vascular corrosion casting studies to meet the need for more in‐depth anatomical insights when using the pig as an animal model in the development of innovative approaches for surgical cardiac ablation in man. The veins from the right cranial and middle lung lobes drain through a common ostium in the left atrium, whereas a second ostium receives the blood returning from all other lung lobes, although limited variation to this pattern was observed. Surrounding anatomical structures that are most vulnerable to ablation damage as reported in man are located at a safer distance from the pulmonary veins in pigs, yet a certain locations, comparable risks are to be considered. Additionally, it was histologically confirmed that myocardial sleeves extend to over a centimetre in the wall of the pulmonary veins.